ChemInform Abstract: Chemical Expansion in SOFC Materials: Ramifications, Origins, and Mitigation. Issue 24 (June 2015) - Bishop, S. R.; Marrocchelli, D.; Perry, N.; Tuller, H. L.; Watson, G.; Yildiz, B.; Amezawa, K.; Kilner, J.
Abstract: Review: 28 refs.